2006
DOI: 10.1103/physrevlett.97.095004
|View full text |Cite
|
Sign up to set email alerts
|

Surface Acceleration of Fast Electrons with Relativistic Self-Focusing in Preformed Plasma

Abstract: We report an observation of surface acceleration of fast electrons in intense laser-plasma interactions. When a preformed plasma is presented in front of a solid target with a higher laser intensity, the emission direction of fast electrons is changed to the target surface direction from the laser and specular directions. This feature could be caused by the formation of a strong static magnetic field along the target surface which traps and holds fast electrons on the surface. In our experiment, the increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 26 publications
4
44
0
Order By: Relevance
“…Other groups have measured beamed electrons in vacuum and suggested that this is due to surface transport. 14,16,17 However, the total number of electrons escaping into vacuum in these experiments is very small and the correlation of those electrons to the internal distribution is weak at best. 18 A simple argument sets the physical limits.…”
Section: A Cone Wall Interactionsmentioning
confidence: 99%
“…Other groups have measured beamed electrons in vacuum and suggested that this is due to surface transport. 14,16,17 However, the total number of electrons escaping into vacuum in these experiments is very small and the correlation of those electrons to the internal distribution is weak at best. 18 A simple argument sets the physical limits.…”
Section: A Cone Wall Interactionsmentioning
confidence: 99%
“…[37][38][39][40] It is thus of interest, for comparison with experimental results, to calculate the electron energy distribution function for different angles with respect to the vacuum-plasma interface. In …”
Section: -5mentioning
confidence: 99%
“…Due to the self-consistently enhanced quasi-static magnetic field and sheath electric field around the surface, the fraction of surface accelerated fast electrons can be enhanced by increasing the total number of the fast electrons generated in the laser-target interaction [10][11][12][13][14][15]. As shown in ref.…”
Section: Textmentioning
confidence: 99%
“…Surface acceleration of fast electrons was observed when the intense short pulse laser beam irradiated the planar target at large incident angle [13][14][15]. PIC simulations and analytical theory [10][11][12] show that a quasi-static surface magnetic field is induced by the fast electrons generated in the interaction via J B × heating or vacuum heating.…”
Section: Textmentioning
confidence: 99%
See 1 more Smart Citation